Analisis Interferensi Pada Laporan Perjalanan Siswa Kelas VIII SMP Negeri 1 Kartasura Dan Implikasinya Dalam Pembelajaran Menulis - Sumarsih, Sri, Prof. Dr. Abdul Ngalim, M.M.,M.Hum (2017)
People around Kartasura is a multilinguals. They interact using more than one language. It can cause a contact of the language. The phenomenon of language contact one of them is interference. Interference is part of sociolinguistic studies. In the learning process, interference includes irregularities that students should avoid. This study aims to identify the form of interference on the student's report in VIII class of SMP Negeri 1 Kartasura. Interference in the report occurs at the morphological, lexical, syntactic, and phonological levels and identifies many factors behind the emergence of such interference. This research includes descriptive research that tries to describe interference when students use Indonesian language. Data collection techniques used are techniques referenced and some other techniques such as interviews, observation, and document analysis. The analysis can be seen that the interferences in student reports include (1) interference in the phonology, (2) morphological, (3) syntax, and (4) lexical. Factors causing interference are habit factors, the development of the times, intentional factors, the influence of the environment, the minimal level of mastery of Indonesian vocabulary, situation factor, and prestige.